Dissolution of Pt and Its Temperature Dependence in Anhydrous Acetonitrile- and Methanol-Based Electrolytes - Ranninger, Johanna; Nikolaienko, Pavlo; Wachs, Susanne; Möller, Jonas; Mayrhofer, Karl; Berkes, Balázs (Journal of The Electrochemical Society, 2020)
Electrode stability is a crucial performance criterion in electrochemistry. Interestingly, in certain fields of electrochemistry, especially when using nonaqueous electrolytes, like in electroorganic synthesis, this aspect remained largely out of focus of investigations so far. Regarding the handling and particularly the purification of nonaqueous electrolytes and the applicable analytical methods to study stability, such fundamental investigations are usually more complicated than in aqueous electrolytes. Herein, we present stability data of Pt metal, as one of the most frequently used electrodes in electroorganic synthesis, in anhydrous (ppm level) acetonitrile- and methanol-based electrolytes in the usually applied potential ranges, obtained using an electroanalytical flow cell (EFC) coupled to an inductively coupled plasma mass spectrometer (ICP-MS). Both electrolyte solvents are widely used in nonaqueous electrochemistry and possess different physico-chemical properties. Here we chose them as representative examples of aprotic and protic solvents and as solvent molecules with two different electrochemical activities: acetonitrile with a wide stability window and methanol being a rather easily oxidizable molecule. A temperature study reveals not only the different electrochemical behavior of the electrolyte systems but also significant differences in Pt dissolution in the studied electrolytes.
CRIS-Team WoS Importer:2020-09-25

Effect of Water Contamination on the Transition Metal Dissolution in Water-Enriched Electrolyte: A Mechanistic Insight into a New Type of Dissolution - Lüchtefeld, Janik; Hemmelmann, Hendrik; Wachs, Susanne; Mayrhofer, Karl; Elm, Matthias T.; Berkes, Balazs B. (Journal of Physical Chemistry C, 2022)
Transition metal (TM) dissolution from cathode active materials is a major factor in accelerating Li-ion battery aging. Residual moisture in the battery is suspected to enhance this degradation mechanism by reacting with the electrolyte, generating acidic species and other decomposition products. In previous studies, we presented a method to track the dissolution in real-time. In the present study, we demonstrate with this method the effect of water on the dissolution of TMs from LiNi0.33Co0.33Mn0.33O2 (NCM111) and LiCoO2 (LCO) used as thin-film model cathodes. We show highly increased dissolution rates in electrolytes with 100 and 1000 ppm of water added and a concomitant decline in electrode performance. More interestingly, we observe a novel hitherto undisclosed dissolution phenomenon during the cathodic back scan and with that give insight into a new dissolution mechanism. This study further reveals that the impact of moisture on TM dissolution may be mitigated by replacing the standard conductive salt, LiPF6, with hydrolysis-stable LiC2NO4F6S2 (LiTFSI).
CRIS-Team Scopus Importer:2022-10-21

On-line monitoring of dissolution processes in nonaqueous electrolytes – A case study with platinum - Ranninger, Johanna; Wachs, Susanne; Möller, Jonas; Mayrhofer, Karl; Berkes, Balázs B. (Electrochemistry Communications, 2020)
Fundamental understanding of electrochemistry in nonaqueous electrolytes is important for applications like nonaqueous batteries, electroorganic synthesis, CO2 reduction, or metal deposition. Studies on electrode stability contribute to our fundamental understanding and are essential for the evaluation of the overall performance of electrochemical systems. With this work we introduce a tool to this field aiming to particularly investigate dissolution of different electrode materials qualitatively and quantitatively in water-free, organic media. The new approach consists of an electroanalytical flow cell with scanning capability on-line coupled to an inductively coupled plasma mass spectrometer, all together optimized to harsh organic environments. As a case study to demonstrate the strength of the method, we have chosen platinum as working electrode. We unveil its dissolution behavior in methanol-based organic electrolytes for the first time under controlled atmosphere (glovebox), and demonstrate differences in dissolution mechanism compared to aqueous electrolytes.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Anodic dissolution; Methanol-based electrolyte; Nonaqueous electrochemistry; On-line dissolution monitoring; Organic ICP-MS; Platinum dissolution

Online Monitoring of Transition-Metal Dissolution from a High-Ni-Content Cathode Material - Wachs, Susanne; Behling, Christopher; Ranninger, Johanna; Möller, Jonas; Mayrhofer, Karl; Berkes, Balázs (ACS Applied Materials and Interfaces, 2021)
The dissolution of transition metals (TMs) from cathode materials and their deposition on the anode represents a serious degradation process and, with that, a shortcoming of lithium-ion batteries. It occurs particularly at high charge voltages (>4.3 V), contributing to severe capacity loss and thus impeding the increase of cell voltage as a simple measure to increase energy density. We present here for the first time the online detection of dissolved TMs from a Ni-rich layered oxide cathode material with unprecedented potential and time resolution in potentiodynamic scans. To this aid, we used the coupling of an electroanalytical flow cell (EFC) with inductively coupled plasma mass spectrometry (ICP-MS), which is demonstrated to be an ideal tool for a fast performance assessment of new cathode materials from initial cycles. The simultaneous analysis of electrochemical and dissolution data allows hitherto hidden insights into the processes' characteristics and underlying mechanisms.
CRIS-Team Scopus Importer:2021-08-06
Keywords: flow cell; ICP-MS; lithium-ion battery; NCM811; online dissolution monitoring; transition-metal dissolution